The Second Five Year Plan Exhibition Souvenir 1958-1959 Pondicherry State - Planning Commission (Planning Commission, 1958)
I have very great pleasure in coming here this evening to inaugurate this exhibition which is the third of its kind. We had already two and it is a matter of very great pleasure for me to be here to inaugurate it not very long after my arrival in Pondicherry. We know that in this country every one is conscious of our Five Year Plan.
Pondicherry State